Supporting English learning activities using hybrid communication and interaction - Kholis, Adhan; Lisan, Khusnul Harsul (Department of Applied Linguistics, FBSB, Universitas Negeri Yogyakarta, 2023)
Covid-19 pandemic extended serious impact toward educational field in all countries. Most schools conducted teaching and learning activities fully online even hybrid to reach the best interaction and communication. This study aimed to explore and describe the implementation of hybrid communication, the benefits, the evaluation and assessment, and the perceptions of both students and parents in English language teaching for the primary education at Afkaaruna Islamic School (AIS) Sleman Yogyakarta, Indonesia. It was qualitative research with a case study research design. In collecting data, the researchers interviewed the principal, the head of curriculum, three English teachers, three students, and parents. The oservation of class activities, the documentation of teaching, and questionnaires of perceptions were also administered as supporting data. In analyzing the data, the researcher used interactive model by Miles & Huberman including data collection, data reduction, data display and conclusions. The results showed that teachers used lab-rotation model (50:50) in teaching and learning. Hybrid communication offered contributions toward English language teaching and learning at primary education including students' enhancement and engagement on English skills, technical skills, class management, and digital literacy as well. Also, it facilitated students to access and obtain many online resources and references such as PDF texts, websites, e-books, YouTube videos, and animations. Moreover, it helped the teachers explained materials easily due to various digital tools used in the classroom. This study is expected to serve as a hybrid learning model for educators as an alternative approach when full online is deemed challenging to implement.